2017
DOI: 10.1080/14767058.2016.1253061
|View full text |Cite
|
Sign up to set email alerts
|

The effect of educational package on functional status and maternal self-confidence of primiparous women in postpartum period: a randomized controlled clinical trial

Abstract: This study showed that training women has a positive effect in increasing their self-confidence and improving their functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Data were collected through a sociodemographic questionnaire, the IFSAC, and the Lips Maternal Self-confidence Score (LMSCS), which was completed before the intervention and six weeks after the intervention. The results of the study showed that education had a positive effect on women's self-esteem and, likewise, affected maternal functioning in a positive manner [19].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Data were collected through a sociodemographic questionnaire, the IFSAC, and the Lips Maternal Self-confidence Score (LMSCS), which was completed before the intervention and six weeks after the intervention. The results of the study showed that education had a positive effect on women's self-esteem and, likewise, affected maternal functioning in a positive manner [19].…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, evaluation of maternal functioning should be included in the postpartum work-up, as it provides valuable information about mother's daily functioning and comfort level in juggling multiple role demands [17]. The studies conducted on Iranian mothers have shown that their functional status is at a moderate level [18,19]. For a woman to fully achieve her postpartum functional status, she must resume most of the roles she had before she gave birth and birth can make it difficult for many women to make a full return to their functional status because of the changes often made in the lives of mothers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors such as anxiety and depression (mental health disorders) can affect maternal recovery and maternal functioning in the postpartum period. Anxiety and depression during the postpartum period can lead to the impaired adjustment of mothers, delay their recovery, and even impede the actions that are necessary to maintain their health [31,43].…”
Section: Discussionmentioning
confidence: 99%
“…In an- other study, the effect of counseling on self-efficacy and short-term breastfeeding outcomes among primiparous mothers in Wuhan, China was assessed, and participants in the intervention group showed significantly more increases in breastfeeding self-efficacy, exclusive breastfeeding and duration of breastfeeding comparing to participants in the control group at 4 and 8 weeks postpartum (30). Also, the results of an interventional study among primiparous women showed that training women has a positive effect in increasing their self-efficacy and improving their functional status (31). The results of a study conducted on 64 male and female high school students in Chaharmahal and Bakhtiari province showed the positive effect of group counseling on self-efficacy (32).…”
Section: Discussionmentioning
confidence: 99%